Observation of the decay B+c → B0sπ+ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
The result of a search for the decay B+c→B0sπ+ is presented, using the B0s→D−sπ+ and B0s→J/ψϕ channels. The analysis is based on a data sample of pp collisions collected with the LHCb detector, corresponding to an integrated luminosity of 1 fb−1 taken at a center-of-mass energy of 7 TeV, and 2 fb−1 taken at 8 TeV. The decay B+c→B0sπ+ is observed with significance in excess of 5 standard deviations independently in both decay channels. The measured product of the ratio of cross sections and branching fraction is [σ(B+c)/σ(B0s)]×B(B+c→B0sπ+)=[2.37±0.31 (stat)±0.11 (syst)+0.17−0.13(τB+c)]×10−3, in the pseudorapidity range 2<η(B)<5, where the first uncertainty is statistical, the second is systematic, and the third is due to the uncertainty on the B+c lifetime. This is the first observation of a B meson decaying to another B meson via the weak interaction.